Pathways of entry and spread of rust pathogens implications for New Zealands biosecurity - Viljanen-Rollinson, S.L.H.; Cromey, M.G. (New Zealand Plant Protection, 2002)
The long distance dispersal of many plant pathogens has been well documented This phenomenon is also common in Australasia with wind currents and movement of people and possibly plant material facilitating introduction of several rust pathogens from Australia to New Zealand The history of the arrival survival and spread of three rust pathogens from Australia to New Zealand is outlined Initial outbreaks of poplar rust in 1973 wheat stripe rust in 1980 and blackberry rust in 1990 are all likely to have been initiated from spores originating in Australia After arrival urediniospores have to be viable and there must be sufficient susceptible hosts and favourable environmental conditions so that initial infection foci can establish and facilitate further spread This information is used to assess the risks posed to New Zealand by other rust pathogens that occur in Australia such as asparagus rust and to assess ways to minimise these risks